Low dielectric resin composition, molded article, film, laminated film, and flexible printed circuit board

By developing a low-dielectric resin composition of liquid crystal polymer and grafted modified polyolefin, forming a sea island structure and a co-continuous structure, the problem of large dielectric loss in the existing low-dielectric resin in high frequency band is solved, and the problem of high dielectric loss in the high frequency band is improved. The melt processability is achieved, and excellent low dielectric characteristics and processing performance are achieved.

CN113767149BActive Publication Date: 2025-02-11KANEKA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202080030452.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2019-04-26
Filing Date
2020-04-23
Publication Date
2025-02-11
Estimated Expiration
2040-04-23

AI Technical Summary

Technical Problem

Existing low-dielectric resins such as liquid crystal polymers have large dielectric losses in high frequency bands and are difficult to melt processing, resulting in the film of the formed product being prone to rupture and the shape of the pellets is uneven.

Method used

Develop a low dielectric resin composition containing liquid crystal polymer and grafted modified polyolefin with polar groups, and optimizes its low Dielectric properties and melt processability.

Benefits of technology

The excellent performance of low dielectric characteristics in high frequency bands is achieved, dielectric loss is reduced, melt processability is improved, and the problems of film prone to rupture and uneven particle shape are avoided.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003314732920000241
    Figure BDA0003314732920000241
  • Figure BDA0003314732920000242
    Figure BDA0003314732920000242
  • Figure BDA0003314732920000251
    Figure BDA0003314732920000251
Patent Text Reader

Abstract

Provided are a low dielectric resin composition having good melt processability and low dielectric properties in a high frequency band that are superior to low dielectric materials such as liquid crystal polymers, a molded product and a film formed by the low dielectric resin composition, a laminated film having a metal foil laminated on at least one main surface of the film, and a flexible printed circuit board comprising the film. A resin composition comprising a liquid crystal polymer (A) and a grafted modified polyolefin (B) having a polar group is used as the low dielectric resin composition. The dielectric constant of the low dielectric resin composition at a frequency of 10 GHz is preferably less than 2.80. The dielectric loss tangent of the low dielectric resin composition at a frequency of 10 GHz is preferably less than 0.0025.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a low dielectric resin composition, a molded product and a film formed from the low dielectric resin composition, a laminated film having a metal foil laminated on at least one main surface of the film, and a flexible printed wiring board including a film formed from the low dielectric resin composition. Background Art

[0002] In recent years, communication devices such as smartphones and electronic devices such as new-generation televisions require high-speed transmission / reception of large amounts of data. In line with this, the high frequencies of electrical signals are being promoted. Specifically, in the field of wireless communications, the introduction of the fifth-generation mobile communication system (5G) is expected around 2020. The use of high-frequency bands above 10 GHz when introducing the fifth-generation mobile communication system is being studied.

[0003] However, as the frequency of the signal used becomes higher, the quality of the output signal may be reduced, which may lead to erroneous recognition of information, that is, the transmission loss becomes larger. The transmission loss includes the conductor loss caused by the conductor and the dielectric loss caused by the insulating resin of the electrical and electronic components such as the substrate in the electronic equipment and communication equipment. The conductor loss is proportional to the 0.5 power of the frequency, and the dielectric loss is proportional to the 1 power of the frequency. Therefore, in the high frequency band, especially the GHz band, the influence caused by the dielectric loss becomes very large.

[0004] Therefore, in order to reduce transmission loss, a low dielectric material with low relative dielectric constant and dielectric loss tangent, which are factors related to dielectric loss, is required. In view of this situation, for example, the use of liquid crystal polymers has been studied as low dielectric materials used in high frequency bands (see Patent Document 1).

[0005] Prior art literature

[0006] Patent Literature

[0007] Patent Document 1: Japanese Patent Application Publication No. 2012-077117 Summary of the invention

[0008] Problem that the invention aims to solve

[0009] However, low dielectric resins such as liquid crystal polymers or compositions thereof are required to have even lower dielectric properties in order to further reduce transmission loss.

[0010] In addition, liquid crystal polymers have a problem of difficulty in melt processing due to their anisotropy. For example, when liquid crystal polymers are made into thin films by extrusion, which is a representative film manufacturing method, the molten liquid crystal polymer discharged from the die immediately sags due to the decrease in melt viscosity caused by the shear force in the discharge direction, making it difficult to collect the film.

[0011] Even if the film can be collected, the resulting film will be very easy to break due to the orientation of the liquid crystal polymer in the film.

[0012] Furthermore, for liquid crystal polymers, it is difficult to produce pellets by cutting strands due to their anisotropy. Specifically, for example, there are problems such as the inability to cut strands, or even if they can be cut, a clean cut surface cannot be formed, and pellets are prone to burrs. The unevenness of the pellet shape and the burrs in the pellets become a factor in the instability of the measurement of the liquid crystal polymer during the molding process of the liquid crystal polymer.

[0013] The present invention has been made in view of the above-mentioned problems, and its object is to provide a low dielectric resin composition having good melt processability and low dielectric properties in a high frequency band that are superior to those of low dielectric materials such as liquid crystal polymers, a molded product and a film formed from the low dielectric resin composition, a laminated film having a metal foil laminated on at least one main surface of the aforementioned film, and a flexible printed circuit board including the aforementioned film.

[0014] Solutions for solving problems

[0015] The present inventors have conducted intensive studies to solve the above-mentioned problems and have completed the present invention.

[0016] That is, the present invention provides the following (1) to (12).

[0017] (1) A low dielectric resin composition comprising a liquid crystal polymer (A) and a graft-modified polyolefin having a polar group (B),

[0018] The low dielectric resin composition has a relative dielectric constant at a frequency of 10 GHz lower than that of the liquid crystal polymer (A) at a frequency of 10 GHz, and a dielectric loss tangent at a frequency of 10 GHz lower than that of the graft modified polyolefin (B) at a frequency of 10 GHz.

[0019] (2) The low dielectric resin composition according to (1), which has a relative dielectric constant of 2.80 or less at a frequency of 10 GHz.

[0020] (3) The low dielectric resin composition according to (1) or (2), wherein the dielectric loss tangent at a frequency of 10 GHz is 0.0025 or less.

[0021] (4) The low dielectric resin composition according to any one of (1) to (3), wherein a sea-island structure including the liquid crystal polymer (A) and the graft-modified polyolefin (B) is formed in at least a portion of the low dielectric resin composition.

[0022] (5) The low dielectric resin composition according to (4), comprising a sea-island structure in which the liquid crystal polymer (A) is a sea component, or a co-continuous structure in which the liquid crystal polymer (A) and the graft-modified polyolefin (B) form a continuous phase together with the sea-island structure.

[0023] (6) The low dielectric resin composition according to any one of (1) to (5), wherein the melting point of the liquid crystal polymer (A) is 250° C. or higher.

[0024] (7) The low dielectric resin composition according to any one of (1) to (6), wherein the polar group is an epoxy group.

[0025] (8) The low dielectric resin composition according to any one of (1) to (7), wherein the graft-modified polyolefin (B) is a polyolefin graft-modified with glycidyl (meth)acrylate and styrene.

[0026] (9) The low dielectric resin composition according to any one of (1) to (8), wherein the graft modified polyolefin (B) has a melting point of 200° C. or higher.

[0027] (10) A molded article formed from the low dielectric resin composition according to any one of (1) to (9).

[0028] (11) A film formed from the low dielectric resin composition according to any one of (1) to (9).

[0029] (12) A laminated film comprising the film according to (11) and a metal foil laminated on at least one main surface thereof.

[0030] (13) A flexible printed circuit board comprising the film described in (11).

[0031] Effects of the Invention

[0032] According to the present invention, which is made in view of the above-mentioned problems, it is possible to provide a low dielectric resin composition having good melt processability and low dielectric properties in a high frequency band that are superior to those of low dielectric materials such as liquid crystal polymers, a molded product and a film formed from the low dielectric resin composition, a laminated film having a metal foil laminated on at least one main surface of the aforementioned film, and a flexible printed circuit board including the aforementioned film. DETAILED DESCRIPTION

[0033] 《Low dielectric resin composition》

[0034] The low dielectric resin composition is a resin composition comprising a liquid crystal polymer (A) and a graft-modified polyolefin (B) having a polar group.

[0035] The relative dielectric constant of the low dielectric resin composition at 10 GHz is lower than the relative dielectric constant of the liquid crystal polymer (A) at a frequency of 10 GHz. In addition, the dielectric loss tangent of the low dielectric resin composition at 10 GHz is lower than the dielectric loss tangent of the graft modified polyolefin (B) at a frequency of 10 GHz.

[0036] The dielectric loss tangent of the low dielectric resin composition at 10 GHz is preferably 0.0025 or less. The lower limit of the dielectric loss tangent is not particularly limited. The lower limit of the dielectric loss tangent may be, for example, 0.0005 or more, or 0.0010 or more.

[0037] In addition, the relative dielectric constant of the low dielectric resin composition at a frequency of 10 GHz is preferably 2.80 or less. The lower limit of the relative dielectric constant is not particularly limited. The lower limit of the relative dielectric constant may be, for example, 2.00 or more, or 2.50 or more.

[0038] The low dielectric resin composition can be suitably used in applications such as electric and electronic parts, information communication devices, and parts of the information communication devices used in high frequency bands by utilizing the low dielectric property.

[0039] The above-mentioned low dielectric resin composition can form various phases depending on various conditions such as the mixing ratio of the liquid crystal polymer (A) and the grafted modified polyolefin (B), the melting point of the liquid crystal polymer (A), the melting point of the grafted modified polyolefin (B), the difference between the melting point of the liquid crystal polymer (A) and the melting point of the grafted modified polyolefin (B), the temperature when the liquid crystal polymer (A) and the grafted modified polyolefin (B) are mixed, and the modification rate of the grafted modified polyolefin (B).

[0040] In the low dielectric resin composition, a sea-island structure including the liquid crystal polymer (A) and the graft modified polyolefin (B) is preferably formed in at least a portion. In the sea-island structure, either the liquid crystal polymer (A) or the graft modified polyolefin (B) may be a sea component.

[0041] Here, the formation of a sea-island structure in at least a portion of the low dielectric resin composition means that when a cross section of a sample of the low dielectric resin composition is observed using an electron microscope (SEM), the sea-island structure is observed in at least one of any three observation target regions of a size of 100 μm×100 μm.

[0042] In this phase, the anisotropy of the properties derived from the liquid crystal polymer (A) is relaxed, and the melt processability of the low dielectric resin composition is good.

[0043] When the above-mentioned sea-island structure is formed in the low dielectric resin composition, the low dielectric resin composition preferably comprises a sea-island structure in which the liquid crystal polymer (A) is the sea component, or a co-continuous structure in which the sea-island structure and the liquid crystal polymer (A) and the graft modified polyolefin (B) form a continuous phase.

[0044] Here, the liquid crystal polymer (A) or the graft modified polyolefin (B) forms a continuous phase means that when a cross section of a sample of the low dielectric resin composition is observed using an electron microscope (SEM), the liquid crystal polymer (A) or the graft modified polyolefin (B) forms an area with an unclosed periphery within the field of view.

[0045] Furthermore, the low dielectric resin composition containing both the sea-island structure and the co-continuous structure means that, when a cross section of a sample of the low dielectric resin composition is observed using an electron microscope (SEM), a co-continuous structure is observed in at least one of any three observation target regions having a size of 100 μm×100 μm and in which the sea-island structure is observed.

[0046] In this case, the liquid crystal polymer (A) forms a sea component or a continuous phase in the co-continuous structure, and thus the low dielectric resin composition easily expresses excellent heat resistance derived from the liquid crystal polymer (A).

[0047] The low dielectric resin composition is produced by mixing a liquid crystal polymer (A) and a graft-modified polyolefin (B).

[0048] The method for mixing the liquid crystal polymer (A) and the graft modified polyolefin (B) is not particularly limited, but a preferred mixing method includes a method using a melt kneading device such as a single-screw extruder or a twin-screw extruder.

[0049] The conditions for mixing the liquid crystal polymer (A) and the graft modified polyolefin (B) are not particularly limited as long as the liquid crystal polymer (A) and the graft modified polyolefin (B) can be uniformly mixed and the components contained in the low dielectric resin composition will not be excessively thermally decomposed or sublimated. When a melt kneading device is used, for example, melt kneading is performed at a temperature preferably 5°C or higher and 100°C or lower than the melting point of the higher melting point of the liquid crystal polymer (A) and the graft modified polyolefin, more preferably 10°C or higher and 50°C or lower.

[0050] The low dielectric resin composition may contain other resins other than the liquid crystal polymer (A) and the graft modified polyolefin (B) within the range that does not hinder the purpose of the present invention. The total ratio of the mass of the liquid crystal polymer (A) to the mass of the graft modified polyolefin (B) relative to the total mass of the resin components contained in the low dielectric resin composition is typically preferably 80 mass%, more preferably 90 mass% or more, further preferably 95 mass% or more, and particularly preferably 100 mass%.

[0051] Examples of other resins include non-liquid crystal polyesters such as polyolefins that have not been grafted, polyethylene terephthalate, and polybutylene terephthalate, polyamides, polyester amides, polyimides, polyamideimides, polycarbonates, polyacetals, polyphenylene sulfide, polyphenylene ether, polysulfones, polyethersulfones, polyetherimides, silicone resins, and fluororesins.

[0052] Inorganic fillers can be mixed into the low dielectric resin composition as needed. As inorganic fillers, calcium carbonate, talc, clay, silicon dioxide, magnesium carbonate, barium sulfate, titanium oxide, aluminum oxide, montmorillonite, gypsum, glass flakes, glass fibers, milled glass fibers, carbon fibers, aluminum oxide fibers, silicon dioxide aluminum oxide fibers, aluminum borate whiskers, and potassium titanate fibers can be listed. The inorganic fillers can be used alone or in combination of two or more.

[0053] The amount of these inorganic fillers can be appropriately determined according to the use of the low dielectric resin composition within the range that does not damage the low dielectric properties of the low dielectric resin composition. For example, when the low dielectric resin composition is used to form a film, the upper limit of the amount of the inorganic filler is determined within the range that does not significantly damage the mechanical strength of the film.

[0054] The low dielectric resin composition may also contain various additives such as organic fillers, antioxidants, heat stabilizers, light stabilizers, flame retardants, lubricants, antistatic agents, colorants, rust inhibitors, crosslinking agents, foaming agents, fluorescent agents, surface smoothing agents, surface gloss improvers, and release improvers as needed.

[0055] These additives may be used alone or in combination of two or more.

[0056] Hereinafter, the liquid crystal polymer (A) and the graft-modified polyolefin (B) will be described.

[0057] <Liquid Crystal Polymer>

[0058] The liquid crystal polymer is a polymer that exhibits optical anisotropy when melted, and polymers recognized as thermotropic liquid crystal polymers by those skilled in the art can be used without particular limitation. The optical anisotropy when melted can be confirmed by a conventional polarization inspection method using crossed polarizers.

[0059] Liquid crystal polymers are typically produced by polycondensing a monomer mixture containing an acylate of a monomer having a phenolic hydroxyl group. The polycondensation is preferably carried out in the presence of a catalyst. Examples of catalysts include metal compounds such as magnesium acetate, stannous acetate, tetrabutyl titanate, lead acetate, sodium acetate, potassium acetate, antimony trioxide, and nitrogen-containing heterocyclic compounds such as 1-methylimidazole.

[0060] The amount of the catalyst used is, for example, preferably 0.1 parts by mass or less based on 100 parts by mass of the monomer mixture (A).

[0061] As described above, the monomer mixture is a mixture of monomers including an acylate of a monomer having a phenolic hydroxyl group. The monomer mixture may include a monomer not having a phenolic hydroxyl group, such as an aromatic dicarboxylic acid represented by terephthalic acid and isophthalic acid.

[0062] As a method for preparing a monomer mixture, a method of acylating a monomer mixture containing a monomer having a phenolic hydroxyl group to obtain a monomer mixture containing an acylate of the monomer having a phenolic hydroxyl group is preferred from the viewpoint of cost and production time.

[0063] Examples of the structural unit constituting the liquid crystal polymer include an aromatic oxycarbonyl unit, an aromatic dicarbonyl unit, an aromatic dioxy unit, an aromatic aminooxy unit, an aromatic diamino unit, an aromatic aminocarbonyl unit, and an aliphatic dioxy unit.

[0064] It should be noted that the liquid crystal polymer may further include an amide bond or a thioester bond as a bond other than an ester bond.

[0065] The aromatic oxycarbonyl unit is a unit derived from an aromatic hydroxycarboxylic acid.

[0066] Specific examples of suitable aromatic hydroxycarboxylic acids include p-hydroxybenzoic acid, m-hydroxybenzoic acid, o-hydroxybenzoic acid, 6-hydroxy-2-naphthoic acid, 5-hydroxy-2-naphthoic acid, 3-hydroxy-2-naphthoic acid, 4'-hydroxyphenyl-4-benzoic acid, 3'-hydroxyphenyl-4-benzoic acid, 4'-hydroxyphenyl-3-benzoic acid, and alkyl, alkoxy or halogen-substituted products thereof.

[0067] Ester-forming derivatives such as ester derivatives and acid halides of aromatic hydroxycarboxylic acids can also be suitably used in the same manner as aromatic hydroxycarboxylic acids.

[0068] Among these aromatic hydroxycarboxylic acids, p-hydroxybenzoic acid and 6-hydroxy-2-naphthoic acid are preferred because the mechanical properties and melting point of the obtained liquid crystal polymer can be easily adjusted.

[0069] The aromatic dicarbonyl repeating unit is a unit derived from an aromatic dicarboxylic acid.

[0070] Specific examples of suitable aromatic dicarboxylic acids include aromatic dicarboxylic acids such as terephthalic acid, isophthalic acid, 2,6-naphthalene dicarboxylic acid, 1,6-naphthalene dicarboxylic acid, 2,7-naphthalene dicarboxylic acid, 1,4-naphthalene dicarboxylic acid, and 4,4′-dicarboxybiphenyl, and alkyl, alkoxy or halogen-substituted products thereof.

[0071] Ester-forming derivatives such as ester derivatives and acid halides of aromatic dicarboxylic acids can also be suitably used in the same manner as aromatic dicarboxylic acids.

[0072] Among these aromatic dicarboxylic acids, terephthalic acid and 2,6-naphthalene dicarboxylic acid are preferred because the mechanical properties, heat resistance, melting point temperature, and moldability of the obtained liquid crystal polymer can be easily adjusted to appropriate levels.

[0073] The aromatic dioxy repeating unit is a unit derived from an aromatic diol.

[0074] Specific examples of suitable aromatic diols include hydroquinone, resorcinol, 2,6-dihydroxynaphthalene, 2,7-dihydroxynaphthalene, 1,6-dihydroxynaphthalene, 1,4-dihydroxynaphthalene, 4,4'-dihydroxybiphenyl, 3,3'-dihydroxybiphenyl, 3,4'-dihydroxybiphenyl, 4,4'-dihydroxybiphenyl ether, and alkyl, alkoxy or halogen-substituted products thereof.

[0075] Among these aromatic diols, hydroquinone, resorcinol, and 4,4′-dihydroxybiphenyl are preferred from the viewpoints of reactivity during polycondensation and the properties of the obtained liquid crystal polymer.

[0076] The aromatic aminooxy unit is a unit derived from an aromatic hydroxylamine.

[0077] Specific examples of suitable aromatic hydroxyamines include aromatic hydroxyamines such as p-aminophenol, m-aminophenol, 4-amino-1-naphthol, 5-amino-1-naphthol, 8-amino-2-naphthol, and 4-amino-4′-hydroxybiphenyl, and alkyl, alkoxy, or halogen-substituted products thereof.

[0078] The aromatic diamino unit is a unit derived from an aromatic diamine.

[0079] Specific examples of suitable aromatic diamines include aromatic diamines such as p-phenylenediamine, m-phenylenediamine, 1,5-diaminonaphthalene and 1,8-diaminonaphthalene, and alkyl-, alkoxy- or halogen-substituted products thereof.

[0080] The aromatic aminocarbonyl unit is a unit derived from an aromatic aminocarboxylic acid.

[0081] Specific examples of suitable aromatic aminocarboxylic acids include aromatic aminocarboxylic acids such as p-aminobenzoic acid, m-aminobenzoic acid, and 6-amino-2-naphthoic acid, and alkyl-, alkoxy-, or halogen-substituted products thereof.

[0082] Ester-forming derivatives such as ester derivatives and acid halides of aromatic aminocarboxylic acids can also be suitably used as monomers for producing liquid crystal polymers.

[0083] Specific examples of the monomer that provides the aliphatic dioxy unit include aliphatic diols such as ethylene glycol, 1,4-butanediol, and 1,6-hexanediol, and acylates thereof.

[0084] In addition, liquid crystal polymers containing aliphatic dioxy units can also be obtained by reacting polymers containing aliphatic dioxy units such as polyethylene terephthalate and polybutylene terephthalate with the above-mentioned aromatic hydroxycarboxylic acids, aromatic dicarboxylic acids, aromatic diols, and their acylates, ester derivatives, acyl halides, etc.

[0085] The liquid crystal polymer may also contain a thioester bond. Examples of monomers that provide such a bond include mercapto aromatic carboxylic acids, aromatic dithiols, and hydroxy aromatic thiols.

[0086] The amount of these monomers used is preferably 10 mol% or less relative to the total amount of monomers providing aromatic oxycarbonyl repeating units, aromatic dicarbonyl repeating units, aromatic dioxy repeating units, aromatic aminooxy repeating units, aromatic diamino repeating units, aromatic aminocarbonyl repeating units, aromatic oxydicarbonyl repeating units, and aliphatic dioxy repeating units.

[0087] Suitable examples of the liquid crystal polymer include the following 1) to 25).

[0088] 1) 4-Hydroxybenzoic acid / 2-hydroxy-6-naphthoic acid copolymer

[0089] 2) 4-Hydroxybenzoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl copolymer

[0090] 3) 4-Hydroxybenzoic acid / terephthalic acid / isophthalic acid / 4,4'-dihydroxybiphenyl copolymer

[0091] 4) 4-Hydroxybenzoic acid / terephthalic acid / isophthalic acid / 4,4'-dihydroxybiphenyl / hydroquinone copolymer

[0092] 5) 4-Hydroxybenzoic acid / terephthalic acid / hydroquinone copolymer

[0093] 6) 4-Hydroxybenzoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl / hydroquinone copolymer

[0094] 7) 2-Hydroxy-6-naphthoic acid / terephthalic acid / hydroquinone copolymer

[0095] 8) 4-Hydroxybenzoic acid / 2-hydroxy-6-naphthoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl copolymer

[0096] 9) 2-Hydroxy-6-naphthoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl copolymer

[0097] 10) 4-Hydroxybenzoic acid / 2-hydroxy-6-naphthoic acid / terephthalic acid / hydroquinone copolymer

[0098] 11) 4-Hydroxybenzoic acid / 2-hydroxy-6-naphthoic acid / terephthalic acid / hydroquinone / 4,4'-dihydroxybiphenyl copolymer

[0099] 12) 4-Hydroxybenzoic acid / 2,6-naphthalene dicarboxylic acid / 4,4'-dihydroxybiphenyl copolymer

[0100] 13) 4-Hydroxybenzoic acid / terephthalic acid / 2,6-naphthalene dicarboxylic acid / hydroquinone copolymer

[0101] 14) 4-Hydroxybenzoic acid / 2,6-naphthalene dicarboxylic acid / hydroquinone copolymer

[0102] 15) 4-Hydroxybenzoic acid / 2-hydroxy-6-naphthoic acid / 2,6-naphthalene dicarboxylic acid / hydroquinone copolymer

[0103] 16) 4-Hydroxybenzoic acid / terephthalic acid / 2,6-naphthalene dicarboxylic acid / hydroquinone / 4,4'-dihydroxybiphenyl copolymer

[0104] 17) 4-Hydroxybenzoic acid / terephthalic acid / 4-aminophenol copolymer

[0105] 18) 2-Hydroxy-6-naphthoic acid / terephthalic acid / 4-aminophenol copolymer

[0106] 19) 4-Hydroxybenzoic acid / 2-hydroxy-6-naphthoic acid / terephthalic acid / 4-aminophenol copolymer

[0107] 20) 4-Hydroxybenzoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl / 4-aminophenol copolymer

[0108] 21) 4-Hydroxybenzoic acid / terephthalic acid / ethylene glycol copolymer

[0109] 22) 4-Hydroxybenzoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl / ethylene glycol copolymer

[0110] 23) 4-Hydroxybenzoic acid / 2-hydroxy-6-naphthoic acid / terephthalic acid / ethylene glycol copolymer

[0111] 24) 4-Hydroxybenzoic acid / 2-hydroxy-6-naphthoic acid / terephthalic acid / 4,4'-dihydroxybiphenyl / ethylene glycol copolymer

[0112] 25) 4-Hydroxybenzoic acid / terephthalic acid / 2,6-naphthalenedicarboxylic acid / 4,4'-dihydroxybiphenyl copolymer.

[0113] As described above, it is preferred that a monomer mixture containing a monomer having a phenolic hydroxyl group is acylated to obtain a monomer mixture containing an acylate of a monomer having a phenolic hydroxyl group. Acylation is preferably performed by reacting the phenolic hydroxyl group with a fatty acid anhydride. As fatty acid anhydrides, for example, acetic anhydride and propionic anhydride can be used. From the perspective of price and handling properties, acetic anhydride is preferably used.

[0114] The amount of the fatty acid anhydride used is preferably 1.0 equivalent or more and 1.15 equivalent or less, and more preferably 1.03 equivalent or more and 1.10 equivalent or less, relative to the amount of the phenolic hydroxyl group.

[0115] A monomer mixture containing a monomer having a phenolic hydroxyl group is mixed with the above-mentioned fatty acid anhydride and heated to perform acylation, thereby obtaining a monomer mixture containing an acylate of the monomer having a phenolic hydroxyl group.

[0116] The monomer mixture containing the acylate of the monomer having a phenolic hydroxyl group obtained above is heated, and the fatty acid by-produced by polycondensation is distilled off, thereby obtaining a liquid crystal polymer.

[0117] When the liquid crystal polymer is produced only by melt polycondensation, the temperature of the melt polycondensation is preferably 150° C. or higher and 400° C. or lower, and more preferably 250° C. or higher and 370° C. or lower.

[0118] When the liquid crystal polymer is manufactured by melt polycondensation and solid phase polymerization described later, the temperature of the melt polycondensation is preferably 120°C or more and 350°C or less, preferably 200°C or more and 300°C or less. The time of the polycondensation reaction is not particularly limited as long as a liquid crystal polymer with a desired melting point or a desired molecular weight can be obtained. For example, the reaction time of the polycondensation is preferably 30 minutes or more and 5 hours or less.

[0119] The liquid crystal polymer produced by the above method may be subjected to polycondensation by heating in a cured state (solid phase) as required in order to further increase the molecular weight.

[0120] By the above method, a liquid crystal polymer (A) is obtained. The melting point of the liquid crystal polymer (A) is not particularly limited within the range that does not hinder the purpose of the present invention. The melting point of the liquid crystal polymer (A) is preferably above 250°C, more preferably above 280°C. On the other hand, from the viewpoint of processability and the aspect of suppressing the decomposition of the grafted modified polyolefin (B) during the manufacture of the low dielectric resin composition, the melting point of the liquid crystal polymer (A) is preferably below 400°C, more preferably below 350°C.

[0121] It should be noted that the melting point of the liquid crystal polymer (A) is, for example, a temperature obtained from a crystal melting peak measured at a heating rate of 20°C / min using a differential scanning calorimeter (hereinafter abbreviated as DSC). More specifically, after observing the endothermic peak temperature (Tm1) observed when the sample of the liquid crystal polymer is measured at a heating condition of 20°C / min from room temperature, it is kept at a temperature of 20°C or higher and 50°C or lower than Tm1 for 10 minutes, and then, after cooling the sample to room temperature at a cooling condition of 20°C / min, the endothermic peak is observed when it is measured again at a heating condition of 20°C / min, and the temperature showing its peak top is taken as the melting point of the liquid crystal polymer. As a measuring device, for example, DSCQ1000 manufactured by TA Instruments can be used.

[0122] <Graft-modified polyolefin (B)>

[0123] The graft-modified polyolefin is not particularly limited as long as it is a resin obtained by graft-modifying a polyolefin and has a polar group.

[0124] Here, the polar group refers to a polar atomic group, which is a group that makes the compound polar when the group exists in an organic compound. Specific examples of polar groups that can be introduced into polyolefins by grafting include carboxyl groups derived from unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, crotonic acid, and isocrotonic acid; acid anhydride groups, halogenated carbonyl groups, carboxylic acid amide groups, imide groups, and carboxylic acid ester groups derived from derivatives of the aforementioned unsaturated carboxylic acids such as acid anhydrides, acid halides, amides, imides, and esters; and carboxylic acid ester groups derived from glycidyl methacrylate, glycidyl acrylate, and monoglycidyl maleate. Ester, diglycidyl maleate, monoglycidyl itaconate, diglycidyl itaconate, allyl succinic acid monoglycidyl ester, allyl succinic acid diglycidyl ester, p-styrene carboxylic acid glycidyl ester, allyl glycidyl ether, methacryloyl glycidyl ether, styrene-p-glycidyl ether, p-glycidyl styrene, 3,4-epoxy-1-butene, 3,4-epoxy-3-methyl-1-butene, and epoxy groups of epoxy-containing vinyl monomers such as vinyl cyclohexene monooxide, etc. Among these polar groups, it is preferred to contain an epoxy group from the perspective of easily obtaining a low dielectric resin composition in a preferred phase and having good adhesion between the low dielectric resin composition and other materials when the low dielectric resin composition is used in contact with other materials.

[0125] The epoxy group can react with the functional groups of the liquid crystal polymer (A), such as phenolic hydroxyl group and carboxyl group. Therefore, the grafted modified polyolefin (B) having the epoxy group as the polar group and the liquid crystal polymer (A) are moderately compatible in the low dielectric resin composition, and can easily form a preferred phase structure such as a sea island structure.

[0126] The island diameter in the sea-island structure is preferably 100 μm or less, more preferably 50 μm or less, and further preferably 10 μm or less. The lower limit of the island diameter is not particularly limited, and may be, for example, 1 μm or more, 2 μm or more, or 3 μm or more.

[0127] As various electrical / electronic devices are becoming smaller and thinner, the film used in the device is sometimes required to have a thickness of, for example, 100 μm or less. Considering that the thickness of the film formed using the low dielectric resin composition is often 100 μm or less, in order to obtain the effect brought by the sea-island structure of the layer structure and suppress the fluctuation of the film characteristics, the island diameter is preferably within the range of 1 μm or more and 100 μm or less.

[0128] It should be noted that "island diameter is less than X μm" means that more than 90%, usually more than 95%, and typically more than 99% of the island phases as a whole of the discontinuous region have a size of less than X μm. In addition, "island diameter is more than Y μm" means that more than 90%, usually more than 95%, and typically more than 99% of the island phases as a whole of the discontinuous region have a size of more than X μm.

[0129] Here, "diameter" generally refers to the diameter of the island. When the shape of the island is significantly different from a circle, the major diameter (the length of the long side of the rectangle circumscribing the island) is defined as the "diameter". Here, the major diameter refers to the length of the long side of the rectangle circumscribing the island, or the length of one side of the square circumscribing the island.

[0130] As a method for confirming the island diameter, for example, the following method can be listed: embedding a thin film formed using a low dielectric resin composition as in the embodiment described later in a thermosetting resin, grinding the cross section in the thickness direction with an ion beam to expose the cross section of the thin film, and observing the cross section of the thin film with a scanning electron microscope.

[0131] The modification amount of the graft modified polyolefin (B) having an epoxy group by the vinyl monomer having an epoxy group is preferably 10% by mass or less, more preferably 5% by mass or less, and further preferably 1% by mass or less. The lower limit of the modification amount by the vinyl monomer having an epoxy group is not particularly limited within the range that does not hinder the purpose of the present invention. The lower limit may be, for example, 0.1% by mass or more, 0.3% by mass or more, or 0.5% by mass or more.

[0132] When the modification amount of the epoxy-containing graft-modified polyolefin (B) by the epoxy-containing vinyl monomer is 0.1 mass % to 10 mass %, a low dielectric resin composition having excellent processability and low dielectric properties can be easily obtained by using the graft-modified polyolefin (B).

[0133] The modification amount by the epoxy group-containing vinyl monomer can be measured using a potentiometric automatic titrator (AT700 manufactured by Kyoto Electronics Co., Ltd.) in accordance with JIS K7236. The modification amount by the epoxy group-containing vinyl monomer can be measured using a graft-modified polyolefin (B) recrystallized from xylene.

[0134] Typically, the graft-modified polyolefin (B) is a resin in which a polyolefin is graft-modified with a vinyl monomer having a polar group in the presence of a radical polymerization initiator.

[0135] The graft-modified polyolefin (B) is preferably a polyolefin graft-modified with a vinyl monomer having a polar group and an aromatic vinyl monomer, and more preferably a polyolefin graft-modified with glycidyl (meth)acrylate and styrene.

[0136] Examples of the polyolefin include chain polyolefins such as polyethylene, polypropylene, poly-1-butene, polyisobutylene, polymethylpentene, propylene-ethylene copolymers, ethylene-propylene-diene copolymers, ethylene / 1-butene copolymers, and ethylene / octene copolymers; and cyclic polyolefins such as copolymers of cyclopentadiene with ethylene and / or propylene.

[0137] Among these polyolefins, polymethylpentene, polyethylene, polypropylene, and propylene-ethylene copolymers are preferred from the viewpoint of easy modification reaction, and polymethylpentene is more preferred from the viewpoint of heat resistance and low dielectric properties.

[0138] Examples of free radical polymerization initiators that can be used when graft-modifying polyolefins include ketone peroxides such as methyl ethyl ketone peroxide and methyl acetoacetate peroxide; peroxyketals such as 1,1-bis(tert-butylperoxy)-3,3,5-trimethylcyclohexane, 1,1-bis(tert-butylperoxy)cyclohexane, 4,4-bis(tert-butylperoxy)butyl valerate, and 2,2-bis(tert-butylperoxy)butane; hydroperoxides such as PERMENTA hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, diisopropylbenzene hydroperoxide, and isopropylbenzene hydroperoxide; dicumyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane, α,α′-bis(tert-butylperoxy)- The free radical polymerization initiator may be any of dialkyl peroxides such as tert-butyl peroxide, di-tert-butyl peroxide, and 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne; diacyl peroxides such as benzoyl peroxide; peroxydicarbonates such as di(3-methyl-3-methoxybutyl peroxydicarbonate) and di(2-methoxybutyl peroxydicarbonate), tert-butyl peroxyoctanoate, tert-butyl peroxyisobutyrate, tert-butyl peroxylaurate, tert-butyl peroxy-3,5,5-trimethylhexanoate, tert-butyl peroxyisopropyl carbonate, 2,5-dimethyl-2,5-di(peroxybenzoyl)hexane, tert-butyl peroxyacetate, tert-butyl peroxybenzoate, and peroxyesters such as di-tert-butyl peroxyisophthalate. The free radical polymerization initiator may be used alone or in combination of two or more.

[0139] The amount of the radical polymerization initiator is not particularly limited as long as the graft modification reaction proceeds well. The amount of the radical polymerization initiator is preferably 0.01 to 10 parts by mass, more preferably 0.2 to 5 parts by mass, based on 100 parts by mass of the polyolefin.

[0140] Examples of vinyl monomers having a polar group that can be used in the graft modification include unsaturated carboxylic acids such as acrylic acid, methacrylic acid, maleic acid, fumaric acid, tetrahydrophthalic acid, itaconic acid, citraconic acid, crotonic acid, and isocrotonic acid; derivatives of these unsaturated carboxylic acids such as anhydrides, acid halides, amides, imides, and esters; and epoxy group-containing vinyl monomers such as glycidyl methacrylate, glycidyl acrylate, monoglycidyl maleate, diglycidyl maleate, monoglycidyl itaconate, diglycidyl itaconate, monoglycidyl allyl succinate, diglycidyl allyl succinate, glycidyl p-styrene carboxylate, allyl glycidyl ether, methacryloyl glycidyl ether, styrene-p-glycidyl ether, p-glycidyl styrene, 3,4-epoxy-1-butene, 3,4-epoxy-3-methyl-1-butene, and vinyl cyclohexene monooxide.

[0141] Among these, epoxy group-containing vinyl monomers are preferred, glycidyl methacrylate and glycidyl acrylate are more preferred, and glycidyl methacrylate is particularly preferred.

[0142] The above-mentioned vinyl monomers having a polar group may be used alone or in combination of two or more.

[0143] The amount of the polar group-containing vinyl monomer used for graft modification of polyolefin is preferably 0.1 to 12 parts by mass, more preferably 0.5 to 10 parts by mass, particularly preferably 1 to 8 parts by mass, based on 100 parts by mass of polyolefin.

[0144] By using the polyolefin modified with the vinyl monomer having a polar group in an amount within the above range, it is easy to obtain a low dielectric resin composition that is in a preferred phase and exhibits desired low dielectric properties.

[0145] As described above, the graft-modified polyolefin (B) is preferably a polyolefin graft-modified with a vinyl monomer having a polar group and an aromatic vinyl monomer.

[0146] This is because the graft reaction is stabilized by using the vinyl monomer having a polar group and the aromatic vinyl monomer in combination, thereby making it easy to graft the vinyl monomer having a polar group in a desired amount.

[0147] Specific examples of the aromatic vinyl monomer include styrene; alkyl styrenes such as o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, β-methylstyrene, dimethylstyrene, and trimethylstyrene; chlorostyrenes such as o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, α-chlorostyrene, β-chlorostyrene, dichlorostyrene, and trichlorostyrene; bromostyrenes such as o-bromostyrene, m-bromostyrene, p-bromostyrene, dibromostyrene, and tribromostyrene; fluorostyrenes such as o-fluorostyrene, m-fluorostyrene, p-fluorostyrene, difluorostyrene, and trifluorostyrene; nitrostyrenes such as o-nitrostyrene, m-nitrostyrene, p-nitrostyrene, dinitrostyrene, and trinitrostyrene; hydroxystyrenes such as o-hydroxystyrene, m-hydroxystyrene, p-hydroxystyrene, dihydroxystyrene, and trihydroxystyrene; and dienylbenzenes such as o-divinylbenzene, m-divinylbenzene, p-divinylbenzene, o-diisopropenylbenzene, m-diisopropenylbenzene, and p-diisopropenylbenzene.

[0148] Among these aromatic vinyl monomers, styrene, α-methylstyrene, p-methylstyrene, o-divinylbenzene, m-divinylbenzene, p-divinylbenzene, or a divinylbenzene isomer mixture is preferred because they are inexpensive, and styrene is particularly preferred.

[0149] The aromatic vinyl monomers may be used alone or in combination of two or more.

[0150] The amount of the aromatic vinyl monomer having a polar group used for graft modification of polyolefin is preferably 0.1 to 12 parts by mass, more preferably 0.5 to 10 parts by mass, particularly preferably 1 to 8 parts by mass, based on 100 parts by mass of polyolefin.

[0151] From the viewpoint of easy melt kneading with the liquid crystal polymer (A), the melting point of the graft modified polyolefin (B) is preferably 80°C or higher, more preferably 100°C or higher, and more preferably 200°C or higher. The upper limit of the melting point of the graft modified polyolefin (B) is not particularly limited, but is preferably 350°C or lower, and more preferably 300°C or lower.

[0152] The low dielectric resin composition described above can be processed into various molded products by various well-known production methods such as injection molding, extrusion molding, blow molding, and solution casting.

[0153] Since the low dielectric resin composition described above is excellent in low dielectric properties in a high frequency band, it is preferably processed into a film and used to produce a flexible printed wiring board with low transmission loss.

[0154] As a suitable method for producing a thin film using a low dielectric resin composition, the following methods 1) and 2) can be mentioned.

[0155] 1) Melt extrusion method using a T-die.

[0156] 2) Solution casting method.

[0157] In the solution casting method, specifically, an organic solvent solution of a low dielectric resin composition is cast on a support, and then the organic solvent is removed from the cast organic solvent solution by heating and / or reducing pressure to obtain a film.

[0158] The casting method is not particularly limited, and known methods such as a die coater, a Comma Coater (registered trademark), a reverse coater, and a knife coater can be cited. As a method for removing the organic solvent, heating is preferred. As a heating method, a method using a known heating device such as a hot air furnace and a far infrared furnace can be cited.

[0159] The organic solvent solution of the low dielectric resin composition is obtained, for example, by mixing the low dielectric resin composition and xylene at a temperature of about 80° C. It is also possible to mix two or more materials constituting the low dielectric resin composition with xylene instead of mixing the low dielectric resin composition with xylene.

[0160] The thickness of the film formed of the low dielectric resin composition is not particularly limited and is appropriately determined according to the application of the film. When the film is used to produce a flexible printed circuit board, the thickness of the film is preferably 5 μm to 200 μm, more preferably 10 μm to 100 μm.

[0161] More specifically, the flexible printed wiring board is typically produced by etching the metal foil in a laminated film in which the film formed of the low dielectric resin composition and the metal foil are laminated to form wiring.

[0162] The flexible printed circuit board has a high transmission speed and a low transmission loss, and therefore can be suitably used as a circuit substrate for high-frequency applications.

[0163] As a method for obtaining a laminated film in which a thin film formed of a low dielectric resin composition and a metal foil are laminated, the following methods I) and II) can be cited.

[0164] I) A method of obtaining a laminated film by thermally pressing a film made of a low dielectric resin composition and a metal foil by heating and pressing.

[0165] II) A method in which an organic solvent solution of a low dielectric resin composition is cast on a metal foil, and the organic solvent is removed from the cast organic solvent solution by heating and / or reducing pressure to obtain a laminated film.

[0166] I), the method and conditions for hot pressing the film formed by the low dielectric resin composition and the metal foil by heating and pressurizing can be appropriately selected from the methods and conditions known in the past. It should be noted that by making the low dielectric resin composition contain a grafted modified polyolefin (B) having a low melting point to a certain extent, the peel strength when peeling the metal foil from the film can be maintained at a high strength of more than 5N / cm, and the hot pressing temperature can be set to a low temperature. As the hot pressing temperature, it is preferably below 400°C, and more preferably below 200°C.

[0167] In the method II), the method of laminating a thin film on a metal foil is the same as the method described above as the solution casting method except that the metal foil is used as a support.

[0168] In addition, in the laminated film, the metal foil may be laminated on at least one main surface of the film, and the metal foil may be laminated on only one main surface of the film or on both main surfaces of the film.

[0169] The metal foil attached to the film formed by the low dielectric resin composition is not particularly limited. Materials for the metal foil used in the manufacture of flexible printed circuit boards for electrical / electronic equipment include copper, copper alloys, nickel, nickel alloys (such as 42 alloy), aluminum, aluminum alloys, and stainless steel.

[0170] Copper foil is preferred as the metal foil used in manufacturing a flexible printed circuit board because of its excellent conductivity, processability, and high bonding strength with a film. As the copper foil, for example, rolled copper foil, electrolytic copper foil, etc. are preferably used.

[0171] If necessary, a functional layer such as a rust-proof layer, a heat-resistant layer, and an adhesive layer may be provided on the surface of the metal foil described above.

[0172] The thickness of the metal foil is not particularly limited and can be appropriately selected depending on the application of the flexible printed wiring board.

[0173] In the laminated film in which the film formed of the low dielectric resin composition and the metal foil are laminated, the peel strength, which is an index of the difficulty of peeling the metal foil from the film, is preferably 5 N / cm or more.

[0174] The peel strength was measured in accordance with "6.5 Peel Strength" of JIS C 6471. Specifically, a 1 mm wide metal foil portion was peeled off at a peeling angle of 90° and a speed of 100 mm / min, and the load during the peeling was measured as the peel strength.

[0175] Example

[0176] Hereinafter, the present invention will be described in more detail with reference to Examples, but the present invention is not limited to these Examples.

[0177] [Production Example 1]

[0178] (Manufacturing of Modified Polyolefin 1)

[0179] 100 parts by mass of (a1) polymethylpentene resin (TPX grade MX002 manufactured by Mitsui Chemicals, Inc.) and 1.5 parts by mass of (b1) 1,3-di(tert-butylperoxyisopropyl)benzene (PERBUTYLP manufactured by NOF Corporation) were supplied from a hopper to a twin-screw extruder ( L / D = 63, Kobe Steel Co., Ltd.) was melt-kneaded, and 8 parts by mass of (c1) styrene and 8 parts by mass of (d1) glycidyl methacrylate were added from the middle of the cylinder. Thereafter, vacuum devolatilization was performed from the exhaust port to obtain pellets of modified polyolefin resin.

[0180] The obtained resin pellets were dissolved in xylene at 130°C and then cooled to room temperature to precipitate a recrystallized resin, and the glycidyl methacrylate modification amount was measured using a potentiometric automatic titrator (AT700 manufactured by Kyoto Electronics Co., Ltd.) in accordance with JIS K7236. The glycidyl methacrylate modification amount of modified polyolefin 1 was 2.64% by mass.

[0181] [Production Example 2]

[0182] (Manufacturing of Modified Polyolefin 2)

[0183] 100 parts by mass of (a1) polymethylpentene resin (TPX grade MX002 manufactured by Mitsui Chemicals, Inc.) and 0.5 parts by mass of (b1) 1,3-di(tert-butylperoxyisopropyl)benzene (PERBUTYLP manufactured by NOF Corporation) were supplied from a hopper to a twin-screw extruder ( L / D = 63, Kobe Steel Co., Ltd.) was melt-kneaded, and 2 parts by mass of (c1) styrene and 2 parts by mass of (d1) glycidyl methacrylate were added from the middle of the cylinder. Thereafter, vacuum devolatilization was performed from the exhaust port to obtain pellets of modified polyolefin resin.

[0184] The obtained resin pellets were dissolved in xylene at 130°C and then cooled to room temperature to precipitate a recrystallized resin, and the glycidyl methacrylate modification amount was measured using a potentiometric automatic titrator (AT700 manufactured by Kyoto Electronics Co., Ltd.) in accordance with JIS K7236. The glycidyl methacrylate modification amount of modified polyolefin 2 was 0.74% by mass.

[0185] [Production Example 3]

[0186] (Manufacturing of Modified Polyolefin 3)

[0187] 100 parts by mass of (a1) polymethylpentene resin (TPX grade MX002 manufactured by Mitsui Chemicals, Inc.) and 2.6 parts by mass of (b1) 1,3-di(tert-butylperoxyisopropyl)benzene (PERBUTYLP manufactured by NOF Corporation) were supplied from a hopper to a twin-screw extruder ( L / D = 63, Kobe Steel Co., Ltd.) was melt-kneaded, and 12.0 parts by mass of (c1) styrene and 12.0 parts by mass of (d1) glycidyl methacrylate were added from the middle of the cylinder. Thereafter, vacuum devolatilization was performed from the exhaust port to obtain pellets of modified polyolefin resin.

[0188] The obtained resin pellets were dissolved in xylene at 130°C and then cooled to room temperature to precipitate a recrystallized resin, and the glycidyl methacrylate modification amount was measured using a potentiometric automatic titrator (AT700 manufactured by Kyoto Electronics Co., Ltd.) in accordance with JIS K7236. The glycidyl methacrylate modification amount of modified polyolefin 2 was 4.29% by mass.

[0189] [Production Example 4]

[0190] (Manufacturing of Modified Polyolefin 4)

[0191] 100 parts by mass of (a1) polymethylpentene resin (TPX grade MX002 manufactured by Mitsui Chemicals, Inc.) and 0.25 parts by mass of (b1) 1,3-di(tert-butylperoxyisopropyl)benzene (PERBUTYLP manufactured by NOF Corporation) were supplied from a hopper to a twin-screw extruder ( L / D = 63, Kobe Steel Co., Ltd.) was melt-kneaded, and 1 part by mass of (c1) styrene and 1 part by mass of (d1) glycidyl methacrylate were added from the middle of the cylinder. Thereafter, vacuum devolatilization was performed from the exhaust port to obtain pellets of modified polyolefin resin.

[0192] The obtained resin pellets were dissolved in xylene at 130°C and then cooled to room temperature to precipitate a recrystallized resin, and the glycidyl methacrylate modification amount was measured using a potentiometric automatic titrator (AT700 manufactured by Kyoto Electronics Co., Ltd.) in accordance with JIS K7236. The glycidyl methacrylate modification amount of modified polyolefin 2 was 0.35% by mass.

[0193] [Examples 1 to 12 and Comparative Examples 1 to 6]

[0194] In the examples and comparative examples, a wholly aromatic liquid crystal polyester resin having a melting point of 280° C. was used as the liquid crystal polymer (A) (component (A)). In addition, in the examples, modified polyolefins 1 to 4 obtained in Preparation Examples 1 to 4 were used as the graft modified polyolefin (B) (component (B)).

[0195] In the comparative example, unmodified polymethylpentene and ethylene / glycidyl methacrylate / methyl acrylate / vinyl acetate copolymer (BONDFAST 7L (BF-7L) manufactured by Sumitomo Chemical Co., Ltd.) were used as the resin mixed with the liquid crystal polymer (A). BONDFAST 7L is a non-graft modified resin having an epoxy group as a polar group.

[0196] The materials in the amounts listed in Tables 1 to 4 were supplied from the hopper port to a twin-screw extruder ( L / D=40, TECHNOVEL CORPORATION) and melt-kneaded to obtain the resin composition of each embodiment and comparative example. It should be noted that, with respect to Comparative Examples 1 to 4, liquid crystal polymer (A), modified polyolefin 1, modified polyolefin 2, or BONDFAST 7L were evaluated separately. With respect to the resin or resin composition of each embodiment and each comparative example, relative dielectric constant, dielectric loss tangent, heat resistance, and processability were evaluated according to the following method. Their evaluation results are recorded in Tables 1 to 4.

[0197] [Relative dielectric constant, dielectric loss tangent]

[0198] As a measuring device, a cavity resonator perturbation method complex dielectric constant evaluation device was used to measure the dielectric constant and dielectric loss tangent of the resin composition obtained at the following frequency.

[0199] Measurement frequency: 10 GHz

[0200] Measurement conditions: temperature 22℃~24℃, humidity 45%~55%

[0201] Measurement sample: A sample left to stand for 24 hours under the above-mentioned measurement conditions was used.

[0202] [Heat resistance]

[0203] As a measuring device, a dynamic viscoelasticity measuring device was used to measure the storage modulus of 10 7 Temperature below MPa (°C).

[0204] Sample measurement range: width 5mm, distance between fixtures 20mm

[0205] ·Measurement temperature range: 25℃~260℃

[0206] Heating rate: 5℃ / min

[0207] Strain amplitude: 0.1%

[0208] ·Measurement frequency: 1Hz

[0209] Minimum tension / compression force: 0.1g

[0210] Initial value of force amplitude: 100g

[0211] [Processability]

[0212] For twin screw extruder ( The strands after melt kneading (L / D=40, manufactured by TECHNOVEL CORPORATION) were water-cooled, and the processability when cut by a pelletizer was evaluated as follows.

[0213] ◎: No cracks or defects, cylindrical pellets can be obtained

[0214] ○: The pellets are partially cracked and flattened.

[0215] ×: The strand cannot be cut to obtain pellets, or most of the pellets have burrs, cracks, or defects.

[0216] [Phase structure]

[0217] The phase structure of each composition was confirmed by microscopic observation. The observation results were classified according to the following criteria. The observation results are recorded in Table 1.

[0218] A: Sea island structure ((A) component is sea)

[0219] B: Sea-island structure ((A) component is an island)

[0220] C: Part of the island structure and co-continuous structure

[0221] D: Phase separation

[0222] [Table 1]

[0223]

[0224] [Table 2]

[0225]

[0226] [Table 3]

[0227]

[0228] [Table 4]

[0229]

[0230] It is clear from the Examples that a composition containing a liquid crystal polymer (A) and a graft-modified polyolefin (B) having a polar group can achieve both good low dielectric properties and excellent melt processability.

[0231] On the other hand, it can be seen from the comparative examples that for the composition formed by using the liquid crystal polymer (A), the grafted modified polyolefin having a polar group, or the non-grafted resin having a polar group alone, or by mixing the liquid crystal polymer (A) with an unmodified polyolefin or a non-grafted resin having a polar group, at least one of the low dielectric properties and the melt processability is poor.

[0232] [Example 13 and Comparative Example 7]

[0233] In Example 13, a double-sided copper-clad laminated film including a film formed of the resin composition and copper foil was obtained using the resin composition obtained in Example 9. In Comparative Example 7, a double-sided copper-clad laminated film was obtained in the same manner as in Example 13 using the liquid crystal polymer (A) described as Comparative Example 1.

[0234] Specifically, a double-sided copper-clad laminate film was produced by the following method.

[0235] As the copper foil, a copper foil having a thickness of 12 μm and a surface roughness Ra of 0.45 μm or less on the surface in contact with the thin film of the resin composition was used.

[0236] The width w of the wiring formed by the copper foil is calculated by the following formula.

[0237] Z=(d / ε×w) 0.5

[0238] In the above formula, Z is the characteristic impedance, which is 50Ω. D is the thickness of the film, which is 100 μm. ε is the dielectric constant of the resin composition.

[0239] The thermal compression bonding conditions were a temperature of 360° C., a pressure of 0.8 tons, and a lamination speed of 1 m / min.

[0240] A microstrip line having a line length of 10 cm was produced using a double-sided copper-clad laminate film obtained by combining a film formed of a resin composition and a copper foil.

[0241] Specifically, after drilling, through-hole plating and patterning steps, a cover film CISV1225 manufactured by NIKKAN INDUSTRIES Co., Ltd. was heated at 160° C. for 90 minutes and bonded, and the pad portion for measurement was gold plated to prepare a microstrip line shaped test piece.

[0242] The obtained test pieces were used to measure the peel strength and the transmission loss.

[0243] For transmission loss, after drying at 150°C for 30 minutes, the test piece was humidified in a test room adjusted to 23°C and 55% RH for more than 24 hours, and then the transmission loss S21 parameter was measured using a network analyzer E5071C (Keysight Technologies) and a probe station (Probe Station) GSG250. The measurement was made in the form of transmission loss (dB / 100mm) at a measurement frequency of 10 GHz.

[0244] The transmission loss of the test piece produced using the double-sided copper-clad laminate of Example 13 was -1.9, and the transmission loss of the test piece produced using the double-sided copper-clad laminate of Comparative Example 7 was less than -2.1.

Claims

1. A low dielectric resin composition comprising a liquid crystal polymer (A) and a graft-modified polymethylpentene having a polar group (B), The graft modified polymethylpentene (B) has a melting point of 200° C. or higher. The low dielectric resin composition has a relative dielectric constant at a frequency of 10 GHz that is lower than the relative dielectric constant of the liquid crystal polymer (A) at a frequency of 10 GHz, and a dielectric loss tangent at a frequency of 10 GHz that is lower than the dielectric loss tangent of the graft-modified polymethylpentene (B) at a frequency of 10 GHz, The low dielectric resin composition has a dielectric constant of 2.80 or less at a frequency of 10 GHz, and a dielectric loss tangent of 0.0025 or less at a frequency of 10 GHz. The low dielectric resin composition forms a sea-island structure including the liquid crystal polymer (A) and the graft-modified polymethylpentene (B) in at least a portion.

2. The low dielectric resin composition according to claim 1, comprising the sea-island structure in which the liquid crystal polymer (A) is a sea component, or comprising the sea-island structure and a co-continuous structure in which the liquid crystal polymer (A) and the grafted modified polymethylpentene (B) form a continuous phase.

3. The low dielectric resin composition according to claim 1 or 2, wherein: The melting point of the liquid crystal polymer (A) is 250° C. or higher.

4. The low dielectric resin composition according to claim 1 or 2, wherein: The polar group is an epoxy group.

5. The low dielectric resin composition according to claim 1 or 2, wherein: The graft-modified polymethylpentene (B) is polymethylpentene graft-modified by using glycidyl (meth)acrylate and styrene.

6. The low dielectric resin composition according to claim 1 or 2, wherein: The total ratio of the mass of the liquid crystal polymer (A) and the mass of the graft-modified polymethylpentene (B) to the total mass of the resin components contained in the low dielectric resin composition is 95 mass % or more. 7 . A molded article formed from the low dielectric resin composition according to claim 1 . 8 . A film formed from the low dielectric resin composition according to claim 1 . 9 . A laminated film comprising the film according to claim 8 and a metal foil laminated on at least one main surface thereof.

10. A flexible printed circuit board comprising the film according to claim 8.

Citation Information

Patent Citations

  • Thermoplastic liquid crystal polymer film and transmission line using the same

    JP2012077117A

  • Liquid crystal polyester resin composition, injection molding product and film comprising the same

    JP1998330602A